The growth of Java bulls fed rice straw and concentrates containing different levels of protein - Retno Adiwinarti; U.R. Fariha; C.M.S. Lestari (Indonesian Center for Animal Research and Development (ICARD), 2011)
This study was performed to determine the growth of Java bulls fed rice straw and concentrates at different levels of protein. Twelve heads of Java bulls, one and a half years old, with initial body weight ranging from 113.83-191 kg were used in this experiment. They were grouped into four replications based on the initial body weight. The rice straw (30%) and concentrates (70%) diet containing three different levels of protein (8.27; 11.03 and 14.43%) were fed during nine weeks. Data gathered were the average daily gain and the average body measurements (chest girth, shoulder height and body length). Result of this study showed that the increase of protein levels from 8.27 to 14,43% did not significantly influence the average daily gain, shoulder height, and body length of Java bulls (P > 0.05), but it influenced daily chest girth (P < 0.05). The average daily gain (ADG), shoulder height and body length were 0.633 kg, 0.08 cm, and 0.09 cm, respectively. The highest average of daily chest girth of Java bulls was T2 = 0.19 cm, followed by T3 = 0.15 cm, and T1 = 0.12 cm. It is concluded that the increase levels of protein from 8.27 to 14.43% did not affect the average daily gain, shoulder height and body length of Java cattle. However, the highest chest girth was achieved by Java cattle which fed concentrate containing 11.03% of protein. Key Words: Growth, Java Bull, Rice Straw, Concentrate, Levels of Protein